AÇÃO CIVIL PÚBLICA COMO INSTRUMENTO PROCESSUAL AMPLIATIVO DOS DIREITOS DA PERSONALIDADE DO TITULAR DE BENEFÍCIO DE PRESTAÇÃO CONTINUADA (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
This article seeks to analyze the role of the Public Civil Action-ACP as a mechanism for the realization of the dignity of the human person and, consequently, of the rights of the personality, based on the importance of the instrument of collective protection for the interpretative progress of the Benefit of Provision Continuous-BPC. With the evolution of two studies and the jurisprudence on the ability of the ACP to protect homogeneous individual rights involving the elderly and people with disabilities, the possibility arises of using the aforementioned action to defend BPC holders. Such a possibility will meet the need to give greater possibility of effectiveness to the BPC, since it is also a fundamental social right. It makes sense to hypothesize that part of this article is that the ACP can be a tool capable of guaranteeing the dignity of the person, with the effectiveness that it also attributes to the protection of the BPC. The methodology used in conducting the research will be the deductive method where, through the bibliographic review of doctrinal works, academic articles, judicial decisions and legislation that affects the theme, the research problem will be explored.